The (Un)Conscious Pariah: Canine and Gender Outcasts of the British Raj - Hamzić, Vanja (Taylor and Francis, 2015)
In the post-1857 colonial era, the Indian social and legal landscape underwent a seismic shift, caused by evermore direct and forceful British rule in many spheres of life, including human-animal and gender relations. This paper provides a brief analysis of this shift through the prism of colonial control of both human and canine pariahs in the Raj, which was fraught with conflicts, debates and moral crises. Since early colonial times, the word ‘pariah’ in the English language has come to denote any person or animal that is generally despised or avoided. It is derived from the Paraiyar (sing. Paraiyan), a low-caste group found in the southernmost part of the Indian subcontinent, which probably owes its name to the Tamil word for a drum (parai). For British colonial masters, however, the word ‘pariah’ was applicable to all of the lowest Indian castes, gender and human outcasts in general and, curiously perhaps, to India’s street dogs. The inherent complexity in the making of the colonial subject—be it the gendered, classed and racialised ‘human’ or, indeed, the non-human ‘animal’—is an often acknowledged fact, which certainly might pose a challenge for historical comparativists. This brief article takes up that challenge and, in doing so, proposes an unorthodox look into the social and political aspects of ‘pariahdom’ in postcolonial studies and beyond. It simultaneously discusses the word ‘pariah’ in a somewhat trans-historical context—one in which its curious ‘social etymology’ and cross-cultural and cross-species semantics point out a type of exclusionary human consciousness.